ENVIRONMENTAL AND NATURAL RESOURCES FUNCTION ZONING FOR SUSTAINABLE USE OF VAN DON ISLAND DISTRICT, QUANG NINH PROVINCE - Thai, Nguyen Dinh; Tue, Nguyen Tai; Hong, Nguyen Thi; Dung, Tran Thi (Vietnam Journal of Marine Science and Technology, 2019)
Van Don district has many favorable conditions in terms of geographical location, economic and political position, and diversity in natural resources for developing marine economic zone. The strength of the district is to develop eco-tourism, conservation of valuable marine ecosystems as well as exploitation of minerals and construction materials. At the present, Van Don is facing negative impacts from urbanization and economic development, environmental degradation, and reduction of biodiversity. Therefore, the purpose of this study aims to determine the zoning criteria and application for the functional zoning for sustainable use of environment and natural resources in Van Don island district. Based on the zoning criteria and natural and socio-economic characteristics, Van Don island district can be divided into two main environmental and natural resources function zones, consisting of Cai Bau island zone (with 3 sub-zones) and Van Hai zone (with 4 sub-zones). Each sub-region has its own unique characteristics that are scientific foundations for orienting sustainable development